Silencing of tropomodulin 1 inhibits acute myeloid leukemia cell proliferation and tumor growth by elevating karyopherin alpha 2-mediated autophagy - Yuan Xia; Dan Wang; Huijie Zhao; Tingyi Meng; Qingling Jiang; Zhaohai Pan; Guoli Wang; Tianyue An; Bohan Li; Sixue Bi; Huikai Wang; Jun Lu; et al. (Elsevier, 2024)
Evidence shows that tropomodulin 1 (TMOD1) is a powerful diagnostic marker in the progression of several cancer types. However, the regulatory mechanism of TMOD1 in tumor progression is still unclear. Here, we showed that TMOD1 was highly expressed in acute myeloid leukemia (AML) specimens, and TMOD1-silencing inhibited cell proliferation by inducing autophagy in AML THP-1 and MOLM-13 cells. Mechanistically, the C-terminal region of TMOD1 directly bound to KPNA2, and TMOD1-overexpression promoted KPNA2 ubiquitylation and reduced KPNA2 levels. In contrast, TMOD1-silencing increased KPNA2 levels and facilitated the nuclear transfer of KPNA2, then subsequently induced autophagy and inhibited cell proliferation by increasing the nucleocytoplasmic transport of p53 and AMPK activation. KPNA2/p53 inhibitors attenuated autophagy induced by silencing TMOD1 in AML cells. Silencing TMOD1 also inhibited tumor growth by elevating KPNA2-mediated autophagy in nude mice bearing MOLM-13 xenografts. Collectively, our data demonstrated that TMOD1 could be a novel therapeutic target for AML treatment.